Fungi resistance of organo‐montmorillonite modified lignocellulosic flour/polypropylene composites. Issue 11 (12th May 2017) - Liu, Ru; Liu, Min; Cao, Jinzhen; Ma, Erni; Huang, Anmin
Abstract : Three types of organo‐montmorillonite (OMMT) modified lignocellulosic fibers/flours reinforced polypropylene (PP) composites were prepared with wood flour (WF), cellulose flour (CF), and lignin flour (LF). The fungi resistance of the composites was tested in laboratory against brown rot ( Gloeophyllum trabeum ) and white rot ( Coriolus versicolor ). The results showed that: (1) except for brown rot of LF/PP composites (with/without OMMT), all composites were showed weight loss after fungi decay. The values were ranging from 0% to 6%, suggesting very good fungi resistance for these composites; (2) the color changes and decreases in flexural property were found after fungi decay, indicating all the composites underwent biodegradation at different extents; (3) compared with brown rot, the composites were easier to be attacked by white rot; (4) for different types of lignocellulosic flours, the effects of OMMT modification were different. POLYM. COMPOS., 39:3831–3840, 2018. © 2017 Society of Plastics Engineers